A new method for predicting of 200, 400, 800, 1500, and 5000 m running records in active young men - Maerfat Siahkohyan; Sohail Mosavi; Elahe Memshali (Shahid Beheshti University, 2019)
Purpose: The aim of this study was to provide a new model for a new model for predicting 200,400, 800, 1500, and 5000 m running records on the Fox & Matthews energy systems in young men.Methods: Fifty active young men (mean ± SD age of 18.11 ± 1.98 years, Height: 171.89 ± 3.27 cm,BMI: 21.11 ± 1.76 kg/m2, VO2max: 51.08 ± 3.67 ml/kg/min) are purposefully selected and wererandomly divided into 5 groups. 100 and 10,000 meters records of all subjects were measured in twoseparate sessions at least with an interval of 72 hours. Then the subject's 200, 400, 800, 1500, 5000m running times in each group were recorded with an interval of 72 hours. Finally, the records werecalculated using the equations based on Fox & Matthews energy systems. Bland-Altman graphicalplots as well as the intraclass correlation coefficient (ICC) statistical tests were used to evaluate theabsolute agreement of the methods.Results: The results showed predictive equations have high agreement with the criterion model(200 m ICC= 0.85, 400 m ICC= 0.83, 800 m ICC= 0.86, 1500 m ICC=0.89 and 500 m ICC=0.81).Conclusion: According to the results of this study it can be concluded that the new model forpredicting 200, 400, 800, 1500, and 5000 m running records can be used as a practical tool forpredicting of distance running records among track and field athletes.